The consequences of protecting audit partners' personal assets from the threat of liability: A discussion - DeFond, Mark L. (Journal of Accounting and Economics, 2012)
In their investigation of UK auditors that voluntarily switch from unlimited to limited liability, Lennox and Li (in this volume, The consequences of protecting audit partners' personal assets from the threat of liability. Journal of Accounting and Economics) provide new insights into a fundamental issue related to audit quality. This discussion attempts to place Lennox-Li into the broader auditing literature and to consider what we learn from their analysis.